Suicidal Thoughts in the Expression of Youngsters’ Consciousness Resulting from the Aggression Suffered in the Family - Kairienė, Brigita (Acta Paedagogica Vilnensia, 2004)
The research has been based on A Maslow's motivation theory according to which aggressive behaviour of parents towards their children is evaluated in the aspect of satisfaction/ non-satisfaction of child's needs, and on the explanation of the suicidal process with regards to the constellation of two identical reasons – the social level and the individual level. It was also aimed at seeing the expression of suicidal thoughts of youngsters who had suffered parents’ aggression. Hypothesis: aggression suffered by youngsters in the family has a negative impact on their consciousness and give rise to suicidal thoughts. The object of research is suicidal thoughts in the expression of 17 years old youngsters. Empiric research defines that the expression of suicidal thoughts of youngsters differs according to gender, i.e. 17-year-old girls have suicidal thoughts more often than boys do. Of all social groups of the youngsters who have taken part in the research, suicidal thoughts are most often seen in the disabled youngsters. With the exception of pupils of the penitentiary institution, suicidal thoughts of other social groups of youngsters occur due to children's' disagreement with their parents, which is most often seen in the case of children's home inmates and the disabled. It has been identified that suicidal thoughts of young people feeling happy in their family are not frequent if compared with those feeling unhappy in their family and often having suicidal thoughts resulting from their disagreement with parents. In the consciousness expression of youngsters who have suffered parents’ aggression, suicidal thoughts more often occur because of their disagreement with parents, if compared with youngsters having less aggression-related experience. The frequency of the suffered aggression is proportional to the frequency of the disagreements with parents, i.e. the wider is the aggression-related experience, the greater is the number of suicidal thoughts.
Keywords: aggressive behavior in the family; suicidal thoughts; physical aggression; psychological aggression